Analisis Penggunaan Aplikasi Pencatatan Keuangan Berdasarkan Teori TAM: (Studi Kasus Pada Online Shop “Sweet Palettee”) - Riza Ahmadina Qawiyyu; Hero Priono (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research was conducted to determine the perception and readiness of an online shop to use a financial accounting application based on the Technology Acceptance Model (TAM) theory. Therefore, interpretive qualitative research was carried out using a descriptive case study approach at the online shop "Sweet Palettee" as the research object. The data collection techniques used were interviews, observation and archival recordings. From the data that has been collected and analyzed by researcher, it is concluded that the use of the financial accounting application carried out by Sweet Palettee based on the Technology Acceptance Model (TAM) theory is going quite well. Each aspect of TAM is interconnected, which overall has a positive role for Sweet Palettee in the acceptance and use of the "Money+" financial accounting application. With this research, it is hoped that it can increase insight and knowledge for researcher and for academics, also can be used as a reference for related companies to make decisions in the future.